Transcranial doppler ultrasonography in children with sickle cell anemia: Clinical and laboratory correlates for elevated blood flow velocities. Issue 2 (26th October 2013) - Lagunju, IkeOluwa; Sodeinde, Olugbemiro; Brown, Biobele; Akinbami, Felix; Adedokun, Babatunde
ABSTRACT Background Transcranial Doppler (TCD) sonography of major cerebral arteries is now recommended for routine screening for stroke risk in children with sickle cell disease (SCD). Methods We performed TCD studies on children with sickle cell anemia (SCA) seen at the pediatric hematology clinic over a period of 2 years. TCD scans were repeated yearly in children with normal flow velocities and every 3 months in children with elevated velocities. Findings were correlated with clinical variables, hematologic indices, and arterial oxygen saturation. Predictors of elevated velocities were identified by multiple linear regressions. Results We enrolled 237 children and performed a total of 526 TCD examinations. Highest time‐averaged maximum flow velocities were ≥170 cm/s in 72 (30.3%) cases and ≥200 cm/s in 20 (8.4%). Young age, low hematocrit, low hemoglobin, and arterial oxygen desaturation <95% showed significant correlations with presence of increased cerebral flow velocities. Conclusions Low hematocrit, low hemoglobin concentration, young age, and low arterial oxygen desaturation predicted elevated cerebral blood flow velocities and, invariably, increased stroke risk, in children with SCA. Children who exhibit these features should be given high priority for TCD examination in the setting of limited resources. © 2013 Wiley Periodicals, Inc. J Clin Ultrasound42:89–95, 2014